Correlated trades and herd behavior in the stock market - Simon Jurkatis; Stephanie Kremer; Dieter Nautz (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2012)
Herd behavior is often viewed as a significant threat for the stability and effciency of financial markets. This paper sheds new light on the relevance of herd behavior for observed correlation of trades. We introduce numerical simulations of a herd model to derive theory-guided predictions regarding the impact of various aspects of uncertainty on herding intensity. We test the predictions using a novel data set including all real-time transactions of institutional investors in the German stock market. In light of the model simulations, empirical results strongly suggest that the observed correlation of trades is mainly due to the common reaction of investors to new public information and should not be misinterpreted as herd behavior.
Keywords: G11; G24; C23; 330; Herd Behavior; Institutional Trading; Correlated Trading; Model Simulation; Herdenverhalten; Aktienmarkt; Institutioneller Investor; Wertpapierhandel; Korrelation; Schätzung; Deutschland